Absorbents, practices, and infrastructures: Changing socio-material landscapes of menstrual waste in Lilongwe, Malawi. (13th October 2022) - Alda-Vidal, Cecilia; Browne, Alison L.
ABSTRACT: In contexts of limited access to urban infrastructures and restrictive cultural norms, managing menstrual waste has important sustainability implications and complicates the menstrual experiences of women. However menstrual waste management has remained largely under-researched. To address this research and policy-practice gap we combine postcolonial and African feminist scholarship with social practice theory to explore the socio-materialities of menstrual waste management in a global South context. Drawing on ethnographic research conducted in Lilongwe we provide a practice-based account of the different strategies followed by women to handle menstrual waste in a changing socio-material context (including changing absorbents, infrastructures, meanings, and interventions). We demonstrate that interventions normalising new types of disposable and reusable absorbents have not incorporated considerations for the implications related to reuse-disposal of new products. Such approaches pass on the responsibility for managing menstrual waste to women and leave them with no 'right' solution as they deal with the unequal infrastructural legacies in the city. We conclude by setting an agenda for research and policy: one that posits that the socio-environmental challenges presented by menstrual waste can be better accounted for by making the needs and desires of women central to the planning of water, sanitation and solid waste services.